Saindo do armário : representação do personagem gay nos filmes de animação "Mary e Max" e "Paranorman" - Santos, Suyene Correia (2016)
This research emerges from the interest to investigate how modes of representation of gay characters in the animated film occur. To observe the characteristics and specificities of these representations, we have chosen as object the characters Damian and Mitch, respectively, from the animated films "Mary and Max" and "ParaNorman" for being the first openly gay characters in this type of film. Firstly, we have based the theoretical study on Stuart Hall, Michel Foucault and Judith Butler to understand the concepts of identity, representation, sexuality and gender. In our theoretical trajectory, it seemed pertinent to note how the representation of gay characters in Hollywood movies and animated film is shaped since their invention to contemporaneity. Therefore, the research developed by Vito Russo and William Mann has contributed regarding the issue. In the empirical field, we have chosen the Content Analysis, supported by Film Analysis, as methodological approach. We have defined five categories, based on the behavioral and psychological aspects of Damian and Mitch; aiming to answer the following questions: 1) what types of representations have emerged from the mediation conducted by the animated films, specifically the corpus of this research? 2) do those representations reaffirm a stereotype or do they trigger new positive social roles ? 3) what is the level of importance of these characters in the plot and how do they relate to their peers? At the end of the analysis, we have concluded that the representation of the gay characters here studied are stereotyped and stigmatized, grounded, somehow, in the heteronormative hegemonic system. Even though, we recognize the importance of the visibility of gay characters in a cultural product such as the animated film, opening paths for a possible awareness of children and young viewers about sexual diversity.